Sosialisasi Literasi Keuangan Syariah Dan Produk Akad Bank Syariah Bagi Masyarakat Desa Pulau Sembilan - Anjur Perkasa Alam Pohan; Khairani Sakdiah; Asmawarna Sinaga (peduli riset dan pengabdian masyarakat, 2023)
Pulau Sembilan is a village in the Pangkalan Susu sub-district, Langkat Regency, North Sumatra province, Indonesia. Although it is often regarded as an area that does not have popular tourist attractions, lately, a very interesting tourist spot in North Sumatra to be used as a recreational destination is Pulau Sembilan in Langkat. This enchanting island has a variety of things that are sure to attract the attention of many tourists to visit it. Even though it is not as popular as other island tourist attractions, its existence cannot be ignored. The method of implementing PKM in the Community Service program carried out by STAI Jam'iyah Mahmudiyah Langkat Lecturers with the Theme: Socialization of Islamic Financial Literacy and Islamic Bank Contract Products for the Pulau Sembilan Village Community, so that youth and the community have the motivation and interest to develop villages by exploring village potential and mobilizing BUMdes as an effort to empower BUMdes and make villages self-sufficient by running the wheels of the village economy through BUMdes. The results of Community Service Activities (PkM) carried out by lecturers and students have an impact on communities with coverage areas that are rarely reached by Islamic financial institutions. They have a better understanding of Islamic banking contracts and products. They can differentiate between Islamic Banks and Cooperatives. As a result, the public's interest in making transactions at Islamic banks has increased. They will open a Sharia Bank account and apply for working capital financing to increase their business. This PkM recommendation needs to provide more intensive assistance in the process of working capital financing to the Mountain communities. Besides that, it is also necessary to carry out the PkM program for Sharia Cooperatives to maintain public trust